Knowledge and attitude on infant oral health among graduating medical students in Nepal - Dhital, Shweta; Pradhan, Megha; Ghimire, Siddharth; Roy, Deepak Kumar; Dahal, Sirjana (Journal of Kathmandu Medical College, 2020)
Background: Overall, children less than five years old are seen more by a physician than a dentist. Physician need more knowledge and skills to address children’s oral health due to the prevalence of dental diseases, the racial and socioeconomic disparities in disease burden, and the restricted access to dental care for many children. Thus, integrating oral health disease prevention and promotion strategies into these medical professionals’ practice becomes essential. Objectives: The objective of this study was to evaluate the knowledge and attitude of graduating medical students of Nepal towards infant oral health. Methods: A self-administered questionnaire included questions on knowledge and attitude regarding infant oral health was distributed to 180 final year MBBS students of Nepal. Data were collected and entered in Microsoft Excel sheet and analysis was done using Statistical Package for the Social Sciences (SPSS) software version 20. Results: The mean age of the participants was 23.36 ± 1.12 years. Only 23.9% of them knew that dental caries is infectious and transmissible from mother to baby and 38.9% were aware of the association of poor maternal gum health and preterm, low birth weight baby. Almost 73.9% knew that gum pads should be cleaned regularly and 46.1% knew that first dental visit of a child should be as soon as the first tooth erupts. Conclusion: This study shows that graduating medical students of Nepal were knowledgeable about some aspects of early childhood caries and infant oral health, but uncertain about other aspects like the association between poor maternal gum health and premature low birth weight babies.